Once more with feeling: On the explanatory limits of the GANE model and the missing role of subjective experience. (2016) - Huntsinger, Jeffrey R.; Storbeck, Justin
Abstract: We applaud Mather and colleagues' model, which emphasizes the neurobiological pathways by which affective arousal tunes attention and memory. This commentary offers a friendly discussion of several potential limitations of the theory. We suggest the model is strong when predicting task-driven demands but is limited when predicting the impact of individual biases, interpretations, and experiential feelings.